Improving corn and soybean yield through fertility and weed management practices - Mueller, Nathan D. (Kansas State University, 2012)
Winter annual weeds (WAW) could affect nitrogen supply for corn production. The objectives of first study were to determine the diversity and abundance of WAW and to evaluate the effect of delaying herbicide applications on nitrogen supply and no-till corn response. Research was conducted in 2010 and 2011 at 14 sites in eastern Kansas. A factorial arrangement of three herbicide application dates (Nov.-Mar., April, and May) and five N rates were used. The three most abundant WAW across sites were henbit, purslane speedwell, and horseweed. Delaying herbicide application until April significantly reduced early corn N uptake by 52 mg N plant-1, chlorophyll meter readings at silking by 3.4%, and grain yield by 0.48 Mg ha-1 across sites. An additional 16 to 17 kg N ha-1 was needed to maintain yield if herbicide application was delayed until April. Starter and foliar micronutrient fertilization can potentially increase corn and soybean yield. The objectives of the second study were to evaluate crop response from combinations of starter and foliar fertilizers that contain N-P-K mixtures with and without a blend of micronutrients at four sites for each crop under irrigated conditions. No early corn growth or yield increase was attributed to application of micronutrients (Fe, Mn, Zn, Cu, and B) beyond what was achieved with N-P-K starter fertilization. There was an increase in soybean height (8 cm) and yield (293 kg ha-1) with starter fertilizer containing N-P-K plus micronutrients over the control. No increase in corn or soybean yield was obtained with foliar fertilization. The objective of the third study was to compare soil mobility and changes in soybean nutrient concentration in the leaf and seed from Mn and Zn sources (EDTA and oxysulfate) at two sites. Zinc sources were more mobile in the soil. Both Zn sources increased seed Zn concentration. Manganese oxysulfate increased seed Mn concentration. However, soybean trifoliolate leaf and seed Mn concentration decreased with soil-applied Na2EDTA and MnEDTA. This response was attributed to formation of FeEDTA and increased Fe supply that reduced root Mn absorption. Manganese EDTA is not recommended for soil application.
Keywords: Micronutrients; Starter fertilizer; Foliar fertilizer; Winter annual weeds; Nitrogen; Survey; Agronomy (0285)